FUN GAMES SEBAGAI BENTUK PLAY THERAPY UNTUK MENGURANGI EMOSI NEGATIF PADA WARGA BINAAN PEMASYARAKATAN RUTAN KELAS I MAKASSAR - Maya Annisa Mursal; Basti Tetteng; Nabilah Assakinah BP; Nabila Putri Anwar; Nabila Ikram; Muhammad Faiz Muttaqi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2022)
Kuliah Kerja Profesi (KKP) are academic activities carried out by students in offices that have a relationship with the student's education department. The KKP which was carried out took place at the Rumah Tahanan Kelas I Makassar which is one of the correctional institutions under the Ministry of Law and Human Rights and is useful for providing security and as a place for fostering Warga Binaan Pemasyarakatan (WBP). Fun Games is one of the work programs with the aim of reducing the negative emotions felt by WBP. The subjects in this activity were 30 Warga Binaan Pemasyarakatan with a range of 18 – 27 years old. This activity can be said to be successful because Warga Binaan Pemasyarakatan feel happy with the games given and based on the results of the satisfaction scale given, that there are 21 people who feel very satisfied, 6 people feel satisfied, and 3 people feel normal.